WATER QUALITY MONITORING AND STATISTICAL ANALYSIS OF THE CHLORINE DIOXIDE WATER TREATMENT SYSTEM PARAMETERS AT THE WATER SUPPLY STATION - BONDARCHUK, OLEKSANDR; SHAKHNOVSKY, ARCADY; SPASIONOVA, LARYSA; MOKIENKO, ANDRIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The paper addresses the research results focused on the collection and analysis of “historical” and evolutionary information related to the operation of the technological water treatment system for the Dnipro River during the implementation of chlorine dioxide as a disinfectant at the Dnipro Water Treatment Plant (located in Kyiv sity). The study was particularly aimed at predicting the condition of the water treatment system, considering the influence of random factors and seasonal changes in natural water quality. Over a two-year period, water quality monitoring was conducted based on a selected set of parameters, and a mathematical analysis of the obtained data was performed. This approach enabled the determination of average values and the range of variation for each water quality indicator under study. The reliability of the numerical statistical estimates (Table 2) is quite high, which is clearly evidenced by the "segments" of the 95% confidence intervals for the mean value and the median. Based on the results obtained, conclusions were drawn that are important for the further operation of the water treatment system at the water treatment plant. Specifically, it was found that during the study period, the quality of drinking water at the system's output met regulatory standards, even in cases of abnormal river water pollution, confirming the effectiveness of the adopted technological solutions and the operation of the implemented network. Thus, the proposed technological solutions and operating regimes of the implemented system are effective in ensuring the epidemiological safety and chemical safety of drinking water following treatment with chlorine dioxide.
Keywords: natural water treatment; water treatment plant; disinfection; chlorine dioxide; monitoring; statistical analysis